On the Origin of the Universe, its Evolution and the Applications Thereof - Michael Swanson (European Journal of Applied Sciences, 2022)
This paper proves the nature of the universe as an apparent contradiction resolving, the consequences and how to utilize them. Included are solutions to the Millennium Prize problems and the Collatz conjecture, a criticism of the current COVID vaccine, and economic and freedom maxima, along with prose that inspires hope for peace and love.